Stage dependent recurrence patterns and post-recurrence outcomes in non-metastatic colon cancer. (2nd September 2021) - Gately, Lucy; Jalali, Azim; Semira, Christine; Faragher, Ian; Croxford, Matthew; Ananda, Sumitra; Kosmider, Suzanne; Field, Kathryn; Lok, Sheau Wen; Gard, Grace; Steel, Malcolm; Lee, Margaret; et al.
Abstract: Background: Multiple meta-analyses have demonstrated that routine surveillance following colorectal cancer surgery improves survival outcomes. There is limited data on how recurrence patterns and post-recurrence outcomes vary by individual tumor stage. Methods: Using a multi-site community cohort study, we examined the potential impact of primary tumor stage on the sites of recurrence, management of recurrent disease with curative intent, and post-resection survival. We also explored changes over time. Results: Of 4257 new colon cancers diagnosed 2001 through 2016, 789 (21.1%) had stage I, 1584 (42.4%) had stage II, and 1360 (36.4%) had stage III colon cancer. For consecutive 5-year periods (2001–2005, 2006–2010, 2011–2016), recurrence rates have declined (23.4 vs. 17.1 vs. 13.6%, p  < 0.001), however, the resection rates of metastatic disease (29.3 vs. 38.6 vs. 35.0%, p  = 0.21) and post-resection 5-year survival (52.0 vs. 51.8 vs. 64.2%, p  = 0.12) have remained steady. Primary tumor stage impacted recurrence rate (3.8 vs. 12 vs. 28%, p  < 0.0001 for stage 1, 2, and 3), patterns of recurrence, resection of metastatic disease, (50 vs. 42 vs. 30%, p  < 0.0001) and post-resection 5-year survival (92 vs. 64 vs. 44%, p  < 0.001). Conclusion: In this community cohort we defined significant differences in recurrence patterns and post-resection survival by tumor stage, with a diminishing rate of recurrence over time. While recurrence rates were lower with stage I and II disease, the high rate of metastatic disease resection and excellent post-resection outcomes help to justify routine surveillance in these patients.